Relationship between gill arch length and standard length for some different feeders of marine fish species, Misurata-Libya (Journal of Academic Research, 2021)
This study investigation the relationship between morphometric of gill arch and standard length of body. In the currently study was used analyzed the morphometric of gill arch and body length in numberous of marine fishes (Scomper scomrus ،Euthynnus alletteratus ،Pagrus pagrus ،Siganus rivulatus ، Coryphaena hippurus). The results of study indicated that, the physical dimensions of gill arches increased isometrically with fish length of all fishes this study. Furthermore, find of positive correlation between length of gill arch and body of all fish species, except S. scomrus which showed negative correlation. These data suggest that, the possibility of using these measurements to find the relationship between the shape and structure of the gill arch apparatus and the nature of food, in addition to their use in differentiating between fish.